How do I prove that the parity operator Af(x) = f(-x) commutes with the second derivative operator. I am tempted to write:(adsbygoogle = window.adsbygoogle || []).push({});

A∂^2f(x)/∂x^2 = ∂^2f(-x)/∂(-x)^2 = ∂^2f(-x)/∂x^2 = ∂^2Af(x)/∂x^2

But that looks to be abuse of notation..

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Parity operator commutes with second derivative?

**Physics Forums | Science Articles, Homework Help, Discussion**